Oral health-related quality of life among pregnant women at Hospital Universiti Sains Malaysia - Ema Yunita Sari; Norkhafizah Saddki; Azizah Yusoff (Syiah Kuala University, 2011)
This cross sectional study aimed to determine oral health-related quality of life in pregnant women. A total of 100 pregnant women seen at the Obstetrics and Gynaecology Clinic at Hospital Universiti Sains Malaysia participated in this study. The short version of the Malaysian Oral Health Impact Profile (S-OHIP(M)) questionnaire with five-point ordinal scale that ranges from ‘never’ to ‘very often’ was used to assess the frequency of oral impacts during the previous 12 months. The majority of the respondents were Malay (96.0%), with a mean age of 29.9 years (SD 5.78). The highest education level attained by most respondents was post-secondary qualification or Diploma (39.0%). Some had formal tertiary education (27.0%). The majority of them were income earners (74.0%) and contributed to the household income. Half of the respondents were in their third trimester of pregnancy while the remaining half was either in the first or second trimester. The severity of impact experienced by the women, which is the mean S-OHIP(M) score was high at 10.43 (95% CI = 8.96, 11.90). The prevalence of impact, which is the percentage of respondents reporting ‘fairly often’ or ‘very often’ to one or more impacts, was 36.0%. Common impacts experienced by the respondents include feeling uncomfortable because food got stuck in between teeth or dentures (22.0%), feeling that oral health problems had caused bad breath (13.0%), and feeling shy because of problems with teeth, mouth or dentures (9.0%). The results also demonstrated that neither the severity nor the prevalence of impact was influenced by the women’s socio-demographic background. This study concluded that pregnant women suffered from high impact of oral diseases that could affect their quality of life